COVID-19 as a force majeure in the context of contractual obligations - Kozień, Kamila (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
The aim of this article is to indicate whether the current pandemic related to the disease caused by the SARS-CoV-2 virus can be recognised from a legal perspectice in the context of contractual obligations. It is essential to consider what force majeure is within the meaning of the civil law and what premises have to be fulfil to recognise the unforeseen circumstance as force majeure. The COVID-19 pandemic exerted, without a doubt, a huge influence on economic turnover. Here comes up a question whether this pandemic can be treated as force majeure justifying an exemption from liability for non-permormance of an obligation or suspension of the time-limit for the period of limitation in connection with an impossibility of prosecution of claims during the pandemic. It should be pointed out that the article is general and it does not involve detailed solutions.